Second Messenger Signaling in Bacillus subtilis: Accumulation of Cyclic di-AMP Inhibits Biofilm Formation - Gundlach, Jan; Rath, Hermann; Herzberg, Christina; Mäder, Ulrike; Stülke, Jörg (Frontiers in Microbiology, 2016)
The Gram-positive model organism Bacillus subtilis produces the essential second messenger signaling nucleotide cyclic di-AMP. In B. subtilis and other bacteria, c-di-AMP has been implicated in diverse functions such as control of metabolism, cell division and cell wall synthesis, and potassium transport. To enhance our understanding of the multiple functions of this second messenger, we have studied the consequences of c-di-AMP accumulation at a global level by a transcriptome analysis. C-di-AMP accumulation affected the expression of about 700 genes, among them the two major operons required for biofilm formation. The expression of both operons was severely reduced both in the laboratory and a non-domesticated strain upon accumulation of c-di-AMP. In excellent agreement, the corresponding strain was unable to form complex colonies. In B. subtilis, the transcription factor SinR controls the expression of biofilm genes by binding to their promoter regions resulting in transcription repression. Inactivation of the sinR gene restored biofilm formation even at high intracellular c-di-AMP concentrations suggesting that the second messenger acts upstream of SinR in the signal transduction pathway. As c-di-AMP accumulation did not affect the intracellular levels of SinR, we conclude that the nucleotide affects the activity of SinR.